Q. Casio Longino, cuestor de la Ulterior (Minerva. Revista de Filología Clásica, 2019)
The present article is about the cursus honorum of Q. Cassius Longinus, quaestor of the Further Spain during the provincial government in absentia of Cn. Pompeius Magnus and later governor of the same country, as well as of the date of their quaestorship (ca. 52 B.C.).